Carlo Marsuppini. Carmi latini Edizione critica, traduzione e commento - PIERINI, Ilaria (Premio Ricerca «Città di Firenze», 2014)
Carlo Marsuppini (1398-1453) is a well known professor at the Studio Fiorentino, Chancellor of the Republic, friend of Cosimo de' Medici and tutor of his children, translator of Homeric and pseudo-homeric works, author of private and, above all, public letters. His activity as a poet is less known: his writings in vernacular were so far entrusted to a handful of poems published in the collection Carmina illustrium poetarum italorum (1720). This book offers for the first time a rigorous critical edition of the humanist's poetic production, based on the analysis of the vast vast known manuscript tradition, and a broad commentary on the individual poems, of which a translation into Italian is also offered.